2009
DOI: 10.1016/j.seizure.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet treatment in adults with refractory epilepsy: A prospective pilot study

Abstract: In our experience with relatively small adult population, adherence to KD is difficult. In patients who had compliance over 3 weeks (6/8), KD does not seem to have a significant effect. Yet, the significant reduction in the two patients who concluded the study per protocol may indicate that some patients may benefit from this diet. Significant increase in LDL levels and the unlikable dietary changes are additional impediments to its implementation among adults with refractory epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 16 publications
3
56
0
Order By: Relevance
“…From the limited studies available, adverse effects appear similar in all age groups; those reported in older patients tend to be non-critical and/or transient and do not lead to stopping treatment 14. One common concern in adults is hyperlipidaemia, but this returns to normal after stopping the diet 19 21. In a recent study, total serum cholesterol and low-density lipoprotein concentrations increased over the first 3 months in adults following the modified Atkins diet, but returned to normal within a year of treatment, even in those taking the diet for >3 years 22.…”
Section: Tolerabilitymentioning
confidence: 99%
“…From the limited studies available, adverse effects appear similar in all age groups; those reported in older patients tend to be non-critical and/or transient and do not lead to stopping treatment 14. One common concern in adults is hyperlipidaemia, but this returns to normal after stopping the diet 19 21. In a recent study, total serum cholesterol and low-density lipoprotein concentrations increased over the first 3 months in adults following the modified Atkins diet, but returned to normal within a year of treatment, even in those taking the diet for >3 years 22.…”
Section: Tolerabilitymentioning
confidence: 99%
“…Weight loss may be an intended positive effect in patients who are overweight, but for those who want to maintain or gain weight adjustments in caloric intake can be made. Increases in serum lipids have been shown to normalize with continued diet therapy (after 1 year) or return to normal after cessation of diet therapy (Cervenka et al, 2016b, Klein et al, 2010, Mosek et al, 2009). In addition, very low carbohydrate diets that induce ketosis have been shown to lead to reductions in serum triglycerides, low-density lipoprotein and total cholesterol and increased levels of high-density lipoprotein cholesterol in adults (Paoli et al, 2013, Sharman et al, 2002).…”
Section: Adverse Effects Compliance and Appropriate Managementmentioning
confidence: 99%
“…31,40 A ketogenic diet can seldom completely replace antiseizure medications because of its limited efficacy, difficulty with longterm diet adherence, and alterations in lipid metabolism over time. 41 This high-fat, adequate-but low-protein, low-carbohydrate diet mimics the effects of fasting and promotes the metabolism of fatty acids to produce ketones. 40 Increased levels of ketones in the brain may lead to a reduction in seizure activity in patients with TSC.…”
Section: Management Of Tsc-associated Epilepsymentioning
confidence: 99%
“…40 Increased levels of ketones in the brain may lead to a reduction in seizure activity in patients with TSC. 41 In a recent study, the effect of the ketogenic diet on the mTOR signaling pathway was investigated in ketogenic diet-fed normal rats and in the rat kainic acidinduced status epilepticus model. 42 In ketogenic diet-fed animals, there was a reduction in the levels of phosphorylated S6 and phosphorylated Aktdanother indicator of mTOR activationdin the hippocampus, suggesting the inhibition of mTOR signaling.…”
Section: Management Of Tsc-associated Epilepsymentioning
confidence: 99%